Influence of earth pressure coefficient, bedding stiffness and ground water level on shallow underground metro station - Magdum, Madan; Karkare, Bilavari (Journal of Structural Engineering, 2024)
Underground metro stations are susceptible to the significant external loads such as earth pressure, water pressure, bedding stiffness and backfill soil cover. The ground imposes formidable challenges in design due to geological complexities, ground water, induced stresses, geological formation history etc. At the initial phase of project, the design is carried based on the available limited geotechnical information. However, further analysed and modified based on the detailed investigation. Hence, it is important to study the influence of earth pressure coefficient at rest (ko), Ground Water Level (GWL) and bedding coefficient (ks) on the design of underground metro stations to establish graphical interaction. The paper presents a parametric soil structure investigation for shallow cut and cover underground metro station having soil cover of minimum 2m on roof. The wide range covers most of the geotechnical conditions across cities in India. 3D Finite element models are analysed considering variation in governing loads and design bending moments at about 20 key locations are presented graphically. The study includes wide range of 132 non-linear 3-D finite element structural models. The sensitivity analysis benefits for optimisation, reducing risk due to uncertainties and to develop the preliminary structural analysis with respect to lower bound and upper bound parameters.